2017
DOI: 10.1016/j.dadm.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of amyloid β in pathologically confirmed frontotemporal dementia syndromes

Abstract: IntroductionThe diagnostic utility of in vivo amyloid β (Aβ) imaging to aid in the clinical distinction between frontotemporal dementia (FTD) and Alzheimer's disease remains unclear without data on the prevalence and severity of Aβ in pathologically confirmed FTD syndromes.MethodsAβ was assessed in 98 autopsy-confirmed FTD and 36 control cases, and the pathological accuracy of 11C-Pittsburgh compound B (PiB)–positron emission tomography imaging was assessed in a subset of FTD cases (n = 15).ResultsAβ was ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 37 publications
4
39
0
1
Order By: Relevance
“…The larger discrepancy in Alzheimer's versus semantic dementia might also reflect a higher prevalence of co-pathologies in Alzheimer's disease versus semantic dementia. Indeed, even though the literature on co-pathologies in semantic dementia is still scarce, autopsy studies revealed that pathologically-confirmed frontotemporal dementia cases with semantic dementia rarely present with co-pathologies such as extracellular amyloid-β (Tan et al, 2017) or Alzheimer's disease pathology (Davies et al, 2005;Mesulam et al, 2014). Recent evidence from animal models even suggests that TDP-43 pathology is associated with reduced amyloid-β burden, possibly due to enhanced amyloid-β clearance (Paolicelli et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The larger discrepancy in Alzheimer's versus semantic dementia might also reflect a higher prevalence of co-pathologies in Alzheimer's disease versus semantic dementia. Indeed, even though the literature on co-pathologies in semantic dementia is still scarce, autopsy studies revealed that pathologically-confirmed frontotemporal dementia cases with semantic dementia rarely present with co-pathologies such as extracellular amyloid-β (Tan et al, 2017) or Alzheimer's disease pathology (Davies et al, 2005;Mesulam et al, 2014). Recent evidence from animal models even suggests that TDP-43 pathology is associated with reduced amyloid-β burden, possibly due to enhanced amyloid-β clearance (Paolicelli et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been obtained previously with PIB in FTD patients and with various amyloid tracers, including florbetapir, in AD patients. We believe that the early florbetapir frames provide important complementary diagnostic information to Aβ deposition, shown by late florbetapir frames, which may be present not only in patients with AD, but also cognitively normal elderly and occasionally as secondary pathology in other neurodegenerative diseases, including FTD [4]. …”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for frontotemporal dementia (FTD), which does not typically present with fibrillar amyloid-beta (Aβ) pathology. However, in some FTD patients, fibrillar Aβ deposits may be present in addition to the pathological hallmarks of FTD and the proportion of cases with both pathologies increases with age [4], therefore an additional differential diagnostic marker is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases amyloid PET can identify fibrillary amyloid as an indicator of AD. Fibrillary amyloid can also coexist with other pathologies, which is frequently the case in patients with DLB and vascular dementia (which might be termed mixed dementia), but is also possible with FTD and may possibly contribute to more rapid progression [451, 452]. Thus, if anti-amyloid therapy did eventually show clinical benefit in AD patients, patients with non-AD dementia and positive amyloid PET might also benefit.…”
Section: Contribution and Role Of Positron Emission Tomography (Pet)mentioning
confidence: 99%